Composition and floristic structure of a portion of dry forest at Tecomán, Colima, Mexico - Guillermo-Sandoval, Eduardo E.; Leopardi-Verde, Carlos L.; Cayetano-Ramírez, Felipe; Alvarado-Segura, Arturo A.; Escobedo-Sarti, G. Jeanett (Instituto de Ecología, A.C., 2021)
A floristic list and an estimate of the community descriptors of a voluntary conservation area located in Tecomán, Colima, are presented to contribute to the knowledge of the vegetation of the dry forests of the Mexican Pacific. The floristic list was built with transects done between 2017-2019. For the community descriptors, the study area was divided into three zones according to their time without management: east slope (LE; without management), central area (AC; 16 years), and west plain (LO; five years); two transects were established in each zone and were sampled during the 2018 dry season. Community and structural descriptors were estimated, and comparisons between the transects were made using an analysis of similarities (ANOSIM); vegetation profiles were based on a transect per area. We found 147 species in 52 families; the richest in species were Fabaceae and Malvaceae with 19 and 14 species, respectively. The descriptors show that the LE is the most diverse (Ds = 0.94 and H’ = 3.00) and equitable (J = 0.93). The most important species were Pachycereus pecten-aboriginum (8.81%) in LE, Acrostichum danaeifolium (14.59%) in AC, and Poaceae family in LO (24.96%). The comparison between the areas suggests that there is an important turnover of species (60% – 80% of the species) and the ANOSIM suggests that there are qualitative differences between them (R = 1.00 and P = 0.07), so the structure and composition of the areas seem to reflect a succession in time and space: LE > AC > LO.